2016
DOI: 10.1021/acs.jmedchem.6b00045
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Molecular Orbital Method Applied to Lead Optimization of Novel Interleukin-2 Inducible T-Cell Kinase (ITK) Inhibitors

Abstract: Inhibition of inducible T-cell kinase (ITK), a nonreceptor tyrosine kinase, may represent a novel treatment for allergic asthma. In our previous reports, we described the discovery of sulfonylpyridine (SAP), benzothiazole (BZT), indazole (IND), and tetrahydroindazole (THI) series as novel ITK inhibitors and how computational tools such as dihedral scans and docking were used to support this process. X-ray crystallography and modeling were applied to provide essential insight into ITK-ligand interactions. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 45 publications
5
81
0
Order By: Relevance
“…This observation is consistent with previous trends for the QM method to predict stronger hydrogen bonds. Our findings corresponded to the attraction energy distribution calculated previously by Heifetz et al for all GPCR‐A crystal structures, which indicated equal electrostatic and hydrophobic character of the orthosteric binding pockets located in the transmembrane‐units …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is consistent with previous trends for the QM method to predict stronger hydrogen bonds. Our findings corresponded to the attraction energy distribution calculated previously by Heifetz et al for all GPCR‐A crystal structures, which indicated equal electrostatic and hydrophobic character of the orthosteric binding pockets located in the transmembrane‐units …”
Section: Discussionsupporting
confidence: 91%
“…The FMO calculations were performed for the ligand and all residues located approximately 4 Å from the ligand. This procedure has been applied successfully to GPCRs by other authors . The FMO input options were set as default.…”
Section: Methodsmentioning
confidence: 99%
“…The FMO methodology was successfully applied to various large biological systems, primarily in a retrospective analysis of binding sites [5][6][7][8][9][10][11][12][13][14][15][16], but also as a tool supporting drug design [17][18][19][20]. Among these, several studies [7,11,16,18] have focused on one of the most important groups of biological targets, a G protein-coupled receptors (GPCRs) family. The authors found crucial interactions that were often ignored by structure-based descriptions and indicated that the FMO scheme would be a valuable tool for structure-based drug design by estimations of the chemical character of the proteins binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an approximate molecular orbital (MO) method called Fragment Molecular Orbital (FMO) was implemented into studies related to GPCR-ligand interactions [60][61][62][63][64][65][66][67][68]. FMO has been described in previous publications and review articles [60][61][62].…”
Section: The Qm Approach In Gpcr Studiesmentioning
confidence: 99%